PERCEPTIONS OF UNDERGRADUATE MEDICAL STUDENTS TOWARDS THE SUBJECT OF PHYSIOLOGY AND LEVEL OF INTEGRATION WITH CLINICAL SUBJECTS - Ali, Zaima; Shakoor, Qamar; Naz, Shaheena; Khalid, Attiqa; Nazir, Sadia; Zaman, Shakila (Pakistan Journal of Physiology, 2016)
Background: Students’ perception of a subject has a very important role in the learning process. Integration of basic medical subjects with clinical sciences generates more interest and enables the students to apply their knowledge clinically. This study aimed to ascertain the medical students’ perception towards physiology as a subject and as a career choice. It also aimed to elucidate students’ perception about level of integration of physiology with clinical and basic subjects. Methods: This was a descriptive study. Students of first till final year participated in the survey by filling a 16 items questionnaire and the responses were graded on a 5 point Likert scale. Results: Physiology was considered an important subject of medical education by all students. Forty-four percent first year students agreed to take up physiology as a future career and the response changed to 24% in the final year students. Majority (78%) of the students were in agreement that integration of physiology with clinical subjects would be fruitful and 71% agreed that it should be integrated in the first year. Conclusion: Instead of teaching physiology as an individual discipline it should be integrated with clinical sciences. This study enlightens importance of integrated medical education. Pak J Physiol 2016;12(2):43–6